Examining the Development of Classroom Assessment Competencies among Pre-Service Teachers: Focus Areas for Universities of Education (Journal of Contemporary Educational Policies and Practices, 2025)
With the rapid advancement of digital technology and particularly artificial intelligence in education, technology-driven teaching and assessment methods are evolving at an unprecedented pace. To keep up with these developments, there is an urgent need to update classroom assessment competencies. The effective development of these competencies should begin with the training provided to students at teacher education institutions. This study employs a proposed measurement scale consisting of four competency domains: Assessment content knowledge (K); Classroom assessment practice skills (P); ICT and digital techniques in educational assessment (I); Ethics (E), to evaluate the classroom assessment competencies of 548 pre-service teachers. The findings revealed significant gaps in the assessment competencies of prospective teachers, particularly in the domains of classroom assessment practice skills and the use of ICT in assessment. These insights provide a strong foundation for recommending improvements to teacher education programs and policies, aiming to better prepare teacher students with essential skills required for effective classroom assessment in the digital age.